EFFECT USING OF FENUGREEK SEEDS AND OLIVELEAVES ON SOME REPRODUCTIVECHARACTERS IN MALE AND FEMALELAYING HENS - Nabeel Ahmad; Sara Alobaidy (Mesopotamia Journal of Agriculture)
This study was conducted to evaluate the effects using Fenugreek seeds (TrigonellaFoenum- Graecum) and Olive Leaves ( Oleaeuropaea L.) on the semen quality ,relative testes weights , relative male and female reproductive system weight and fertility rate .Ninety females and 18 males of ( ISA Brown Laying hen breeder were used in this study (84 week old) ,birds were divided into 3 groups each group consists of 30 hens and 6cock ,6 replicates (5hens and1cock replicate) , and treated as follows for 16 weeks : Trt1 : Control diet. Trt2 : Control diet + (10gm kg) of diet Fenugreek seeds . Trt3 : Control diet + (10gm kg) of diet Olive leaves . Result showed significant deference in the semen volume in first period as compared with second period , semen volume decrease with age , a significant increase were also observed in second period for trt (massmotility ,abnormal permsandsperm concentration ml as comparedwith the firstperiod . Results also revealed thatFenugreek seed and Olive leaves treatment causes a significant improvement in all semen characters as compared with control , and enhance thefertility rate in both normal and artificial insemination .Results also revealed olive leavestreatment asignificant in the relative female reproductive system weightas compared Fenugreek seed and control group.